Cortisol intermediates and hydrocortisone responsiveness in critical neonatal disease. (18th July 2017) - Khashana, Abdelmoneim; Saarela, Timo; Ramet, Mika; Hallman, Mikko
Abstract: Objective : Therapy-resistant hypotension complicates diseases in neonates. Our objective was to investigate whether lack of therapeutic response to plasma expanders and inotropes associates with serum levels of cortisol and its precursors. Methods : We investigated 96 infants with hypotension and critical neonatal disease for cortisol metabolism and are divided into responders and non-responders to plasma expanders and inotropes. Serum concentrations of steroids were analysed soon after the onset of volume expansion and inotrope treatment for shock. The 48 non-responders were treated with intravenous hydrocortisone (HC) and serum cortisol concentrations were monitored a week later. Results : The mean cortisol concentrations did not differ between the responders and non-responders: 13.6 ± 2.5 and 12.5 ± 4.5 μg/dL, respectively. Dehydroepiandrosterone (37.3 ± 19.5 versus 324.0 ± 106.3; p < 0.0001) and 17-hydroxy-pregnenolone concentrations were lower in responders than in non-responders. Dehydroepiandrosterone levels in non-responders were inversely associated with postnatal age ( r = 0.50, p < 0.0001). There were no differences in 17-hydroxy-progesterone, 11-deoxy-cortisol and cortisone between the responders and non-responders. Hydrocortisone administration acutely increased blood pressure. Six non-responders who died despite HC administration had low levels of cortisol. The responders had normal serum cortisol after HC treatment. Conclusion : Precursors of cortisol, proximal to the 3β-hydroxysteroid dehydrogenase activity, accumulated in neonates with hypotension, responding to HC treatment.